Identifying the challenges in SCM: Evidence from Mangaung Metropolitan Municipality - Tafadzwa. C. Maramura; Joseph. M. Ruwanika (Cogent Business & Management, 2023)
Supply Chain Management (SCM) fulfils an important role in the economy and public expenditure of a country and can be regarded as a critical factor for the efficiency of a government because it is a main component of public service delivery. Since the introduction of the SCM policy in South African public sector it has been faced with a myriad of challenges which are hampering service delivery. This study aims to investigate the challenges in supply chain management, affecting service delivery in the Mangaung Metropolitan Municipality (MMM). The study was qualitative in design. Semi-structured interviews were used, and the data was thematically analysed. One of the findings of this study is that the SCM department cannot function properly if there are instability, lack of integrity, lack of human capacity, lack of skills, non-payment of suppliers, political interference, corruption, and lack of accountability. The supply chain management system should move from a paper-based system to an electronic system to allow for effective and efficient service delivery. Public officials should be able to interpret the acts, rules, and regulations, as well as policies, governing SCM. The study recommended that, to improve service delivery, there is a need to hire people in supply chain management who have the capacity and skills to do the job. The study also recommended that, internal controls need to be strengthened in all areas of SCM and legislation needs to be reviewed to allow for the quicker procurement of goods and services.
Keywords: 650; Commodities; Legislation; Public Service; Service Delivery; Supply Chain Management